Dişi köpeklerde östrus siklusunun farklı dönemlerindeki serum Vitamin E ve malondialdehit düzeyleri ile bazı üreme özelliklerinin değerlendirilmesi (The Evaluation of Some Reproductive Parameters and Serum Concentrations of Vitamin E and Malondialdehyde in Different Stages of Estrus Cycles in Bitches) - Zonturlu, Ak; Sönmez, M; Türk, G; Yüce, A (My University, 2010)
This study was performed to determine whether there is a relationship between some reproductive traits and the serum concentrations of vitamin E and malondialdehyde (MDA) in different stages of estrus cycles in bitches. A total of 19 multiparous bitches (8 Labrador Retrievers and 11 German Shepherds) were used in this study. The onset of proestrus was designated as the first day of sanguineous vaginal discharge. Following that, vaginal smears were obtained from each bitch daily until onset of diestrus. Blood samples were collected in the onset of proestrus, estrus and diestrus and, serum concentrations of vitamin E and MDA were determined. The bitches were naturally mated on day 2 and 4 after onset of estrus. There was no significant difference (P>0.05) in the serum concentrations of vitamin E and MDA in different stages of estrus cycles although there was individual difference among bitches. In addition, there was no relationship between litter size and other reproductive traits and the serum concentrations of vitamin E and MDA. There was a negative correlation (P<0.01 r=-0,829) between the length of gestation and litter size. In conclusion, we observed that the serum concentration of vitamin E and MDA was similar in different stage of cycles and, they had no significant effect on the reproductive traits in bitches.
Makale - Bilimsel Dergi Makalesi - Çok Yazarlı
Keywords: Köpek östrus vitamin E malondialdehit yavru sayısı (Bitch estrus vitamin E malondialdehyde litter size)